Thermodynamic Properties and Glass Transition Temperature of Roasted and Unroasted carob (Ceratonia siliqua L.) powder - Červenka, Libor; Anna, Stepien; Frühbauerová, Michaela; Velichová, Helena; Witczak, Mariusz (Elsevier, 2019)
Moisture adsorption isotherms of unroasted and roasted carob powder (Ceratonia siliqua L.) at 15, 25, and 40 °C were determinated by the static gravimetric method over the wide range of water activity from 0.06 to 0.90. GAB model fitted well the experimental adsorption data showing sigmoid shape curves for both samples. Claussius-Clapeyron equation showed that the adsorbed moisture is strongly bound to the surface of unroasted carob powder in low moisture content than that in roasted sample. The variation of the net integral enthalpy and entropy with the moisture content exhibited maximal and minimal values for unroasted carob powder at low moisture content, respectively. Combining the glass transition temperature lines with adsorption isotherms, it was found that roasted carob powder is stable up to 0.43 aw in comparison with unroasted carob powder (up to 0.38 aw). Additionally, higher content of phenolics was observed in roasted carob powder.
Termodynamické vlastnosti a teplota skelného přechodu u praženého a nepraženého karobového prášku
Keywords: carob; compensation theory; differential calorimetry; storage condition; karob; kompenzační teorie; diferenční kalorimetrie; skladovací podmínky